Lecithin as a therapeutic agent in Ulcerative Colitis - Stremmel, Wolfgang; Gauss, Annika (Digestive diseases, 2013)
Lecithin [phosphatidylcholine (PC)] was shown to account for more than 70% of total phospholipids within the intestinal mucus layer. It is arranged in lamellar membranes (surfactant-like particles) and establishes a hydrophobic barrier preventing invasion of the colonic commensal microbiota. In ulcerative colitis (UC), the mucus PC content was demonstrated to be reduced by about 70%, irrespective of the presence of inflammation. This may be of primary pathogenetic significance allowing bacteria to enter the mucus and induce mucosal inflammation. Therefore, a new therapeutic strategy is being developed to substitute the missing mucus PC content in UC. Indeed, a delayed-release PC formulation was able to compensate the lack of PC and improve the inflammatory activity. In randomized controlled studies, delayed-release PC was proven to be clinically and endoscopically effective, which now awaits a phase III authority approval trial.